Clinical outcome of post placental IUD CuT380 insertion in terms of expulsion - Shabbir, Quratulain; Usman, Amna; Yasmeen, Attiya; Zafar, Humaira; Naz, Falak; Faisal, Sanober (International Journal of Research in Medical Sciences, 2021)
Background: Insertion of an intrauterine contraceptive device (IUD) immediately after delivery has been recommended by the World Health Organization (WHO), as one of the safe and effective methods of temporary contraception. In the immediate post delivery period the women are highly motivated and need an effective method for contraception so that the child can be brought up with a relaxed mind without the worry of unintended pregnancy. This approach is more applicable to our country where delivery may be the only time when a healthy woman comes in contact with health care personnel. However, immediate post-partum IUD insertion may have disadvantages as well. The risk of spontaneous expulsion may be unacceptably high. Methods: After taking approval from hospital ethical committee, all women planning vaginal delivery desiring IUD, admitted through OPD and emergency were evaluated in detailed on design Performa Performa include patient’s identity, age, parity, gestational age, no of alive children, outcome and timings of insertion. Informed consent was obtained. With aseptic precautions IUD was inserted with kellys forceps in the uterine cavity up to the fundus, then cervix was examined for thread (that should not be visible at cervix if proper insertion done). The procedure was performed by myself. Patients were followed at 6week by examining the threat of IUD. All the information was recorded by myself. Follow up was done by taking patients contact number. Results: In our study, out of 300 cases, 63.67% (n=191) were between 18-30 years of age while 36.33% (n=109) were between 31-40 years of age, mean+sd was calculated as 29.49+4.62 years, mean gestational age was calculated as 38.53+0.94 weeks, mean parity was calculated as 3.49+1.06 paras. Frequency of expulsion in post placental intra uterine device cuT 380 insertions reveals in 8.67% (n=26). Conclusions: We concluded that the frequency of expulsion in post placental intra uterine device cuT 380 insertions is not significantly higher and appears to be safe and effective method of contraception.